2007
DOI: 10.1002/cncr.22912
|View full text |Cite
|
Sign up to set email alerts
|

BRAFV600E mutation and p27kip1 expression in papillary carcinomas of the thyroid ≤1 cm and their paired lymph node metastases

Abstract: BACKGROUND. BRAFV600E mutation and p27kip1 expression have been introduced as novel indicators that may predict prognosis in different tumors, as well as in papillary thyroid carcinomas. METHODS. Tissue samples from 214 consecutive patients who underwent total or near‐total thyroidectomy with histological diagnosis of papillary thyroid carcinoma (PTC) ≤1 cm were analyzed for BRAFV600E mutation by a real‐time, allele‐specific amplification and for p27kip1 expression by immunohistochemistry. RESULTS. The BRAFV60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
64
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 25 publications
5
64
4
Order By: Relevance
“…In our previous work, BRAF V600E mutation was evaluated in a series consecutive of patients by a real-time, allele-specific amplification essentially as described by Jarry et al 21,22 Here we randomly selected 27 patients from the described group. Age of the 27 patients who underwent surgery for the classical variant of papillary thyroid carcinoma ranged from 17 to 76 years (median age was 48 years), and there was a strong predominance of female patients (81%).…”
Section: Case Selectionmentioning
confidence: 99%
“…In our previous work, BRAF V600E mutation was evaluated in a series consecutive of patients by a real-time, allele-specific amplification essentially as described by Jarry et al 21,22 Here we randomly selected 27 patients from the described group. Age of the 27 patients who underwent surgery for the classical variant of papillary thyroid carcinoma ranged from 17 to 76 years (median age was 48 years), and there was a strong predominance of female patients (81%).…”
Section: Case Selectionmentioning
confidence: 99%
“…At variance with RET/ PTC, BRAF (V600E) positive PTCs were not found to be in relationship to previous radiation exposure (Nikiforova et al 2004); no other environmental factors has been identified that favors BRAF (V600E) mutation. Several studies tried to establish a correlation between BRAF (V600E) and the clinical features of PTCs, but results have been controversial (Lee et al 2007, Xing 2007: in some studies, BRAF (V600E) was associated with a more advanced tumor or a more aggressive phenotype (Namba et al 2003, Nikiforova et al 2003, Kim et al 2004, 2006a,b, Oler et al 2005, Powell et al 2005, Jin et al 2006, Riesco-Eizaguirre et al 2006, Kebebew et al 2007, Rodolico et al 2007, while other studies did not find this association (Fugazzola et al 2004, Puxeddu et al 2004, Kim et al 2005, Liu et al 2005, Trovisco et al 2005, Jo et al 2006, Park et al 2006, Sapio et al 2006, Abrosimov et al 2007, Durante et al 2007, Mitsiades et al 2007; see Table 1). Kim et al (2006a) 203 Korea Kim et al (2006b) 103 USA (CA) 100 Korea Riesco-Eizaguirre et al…”
Section: Introductionmentioning
confidence: 99%
“…67 Spain Giannini et al (2007) 69 Italy Kebebew et al (2007) 274 USA (CA) Lupi et al (2007) 500 Italy Rodolico et al (2007) Discrepancies between those studies, however, may depend on heterogeneous series of tumors, including different PTC variants and tumors from different geographical areas (Lee et al 2007, Xing 2007. BRAF (V600E) is also the most common genetic alteration occurring in micro-PTCs (w30-50% of cases; Sedliarou et al 2004, Barbaro et al 2005, Trovisco et al 2005.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown the positive relationship between BRAF V600E mutation and other aggressive factors, such as extrathyroidal extension, LNM, high TNM stages, and recurrence [11][12][13]. Thus, BRAF V600E mutation is considered as a powerful biomarker for predicting poor prognosis.…”
mentioning
confidence: 99%